Health-risk assessment for roof-harvested rainwater via QMRA in Ikorodu area, Lagos, Nigeria - Chukwuemeka Kingsley John (IWA Publishing, 2021)
This paper presents a study to assess the roof-harvested rainwater (RHRW) in the Ikorodu area of Lagos state, Nigeria, and recommends guidance to minimise the health risk for its households. The types, design and use of rainwater harvesting systems have been evaluated in the study area to inspect the human risk of exposure to Escherichia coli (E. coli). To achieve these objectives, a detailed survey involving 125 households has been conducted which showed that 25% of them drink RHRW. Quantitative microbial risk assessment (QMRA) analysis has been used to quantify the risk of exposure to harmful E. coli from RHRW utilised as potable water, based on the ingestion of 2 L of rainwater per day per capita. Results have revealed that the maximum E. coli exposure risk from the consumption of RHRW, without application of any household water treatment technique (HWTTs) and with application of alum only, were 100 and 96 respectively, for the estimated number of infection risk per 10,000 exposed households per year. This estimation has been done based on 7% of E. coli as viable and harmful. Conclusively, it is necessary that a form of disinfectant be applied to the RHRW before use. HIGHLIGHTS It consists of a case study of roof-harvested rainwater at Ikorodu area of Lagos, Nigeria.; The QMRA analysis has been used to quantify the risk of infection associated with the exposure to potential pathogens from roof-harvested rainwater.; This paper presents a pilot rainwater quality study at the investigated area, which involves a detailed household surveying technique to acquire the needed research information.;